ANALISIS PENGARUH FASILITAS BELAJAR TERHADAP PRESTASI BELAJAR SD KELAS V - Muansar S. Bakar; Munandar M. Abdullah; Mi'raj kamahi; Mukmin Amsidi (Jurnal Edukasi, 2026)
Analysis of the influence of learning facilities on the learning achievement of fifth grade students at UPTD Sd Inpres Umapura. Thesis, elementary school teacher education department, STKIP Muhammadiyah Kalabahi (Supervised by Ayahanda Mi'raj Kamahi and Ayahanda Munandar M. Abdullah). This study examines the analysis of the influence of learning facilities on the learning achievement of fifth grade elementary school students at UPTD Sd Inpres Umapura. The researcher's objectives (1) To find out the description of the learning facilities of fifth grade elementary school students at Umapura Inpres (2) To find out the description of the learning achievement of fifth grade elementary school students at Umapura Inpres (3) To find out the influence of facilities on the learning achievement of fifth grade elementary school students at Umapura Inpres. This study is a quantitative study with the type of Expo Facto research. The population in this study amounted to 135 students and the number of samples was 16 students. The instruments given, previously carried out validity tests and prerequisite tests, namely: Normality test, homogeneity test, hypothesis test. Using (SPSS). Statistical Product and Service Solutions Version 24